Branding Brondong Ketan: From Traditional Snack to Competitive MSME Product - Unsi, Baiq Tuhfatul; Nadiroh, Intan; Arifah, Nur; Azizah, Nur; Zuhroh, Naila Izzatuz (Universitas Nurul Jadid, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting rural economies, yet many traditional products remain underdeveloped due to weak branding and limited digital marketing. This community engagement program aimed to transform Brondong Ketan in Ngumpak Hamlet through branding and packaging innovation based on the Asset-Based Community Development (ABCD) approach. The primary problems faced by partners were low monthly turnover (Rp 300,000–500,000), unattractive packaging, and reliance on local distribution channels. The program was implemented collaboratively in five stages—discovery, dream, design, define, and destiny—through activities such as branding workshops, co-creation of new batik-accented packaging, and digital promotion using WhatsApp Business. The results demonstrated a significant improvement: average monthly revenue increased up to ±Rp 1,250,000 (around 300% growth), with about 25% of customers from outside the village and 20% of sales made through WhatsApp. Furthermore, an informal working group was established, and a local champion actively facilitated collective marketing, coordinated production, and promoted digital advocacy among producers. These outcomes indicate that asset-based empowerment fosters sustainable innovation, strengthens cultural identity, and enhances MSME competitiveness in broader markets.